Factors affecting the productivity of Djallonke sheep in Mali - Niare, T.; Dembélé, I.; Traoré, M.I. (1989)
Two village flocks of Djallonke sheep were studied during a two year period to evaluate reproductive performance, describe management methods and to analyse flock structure. Age at first lambing was 15 months but was very variable. The fertility rate of 77 per cent showed that very few females gave birth twice in the one year. Lambing intervals varied between flocks and between years. The number of multiple births was very low and the litter size average 1.05. A preliminary evaluation of these components led to an indication of numerical productivity of 0.81 lambs born live per female per year. This productivity could be improved and some indications of how this may be achieved are given.